Seroprevalence and Risk Factors of Small Ruminant Brucellosis in West Hararghe Zone of Oromia Regional State, Eastern Ethiopia - Umer Seid Geletu; Munera Ahmednur Usmael; Yesihak Yusuf Mummed (Veterinary Medicine International)
A cross-sectional study design was employed on collected sera samples to investigate brucellosis in small ruminants from December 2018 to November 2019 with the objectives of estimating the seroprevalence and potential risk factors for the occurrence of brucellosis in small ruminants in selected districts of West Hararghe: Chiro, Hirna, and Mieso. A total of 2070 collected sera samples from small ruminants were tested using serological tests and screened by RBPT and confirmatory test (CFT). The overall seroprevalence of the present study was 0.24% in small ruminants (Chiro 0.2%, Hirna 0%, and Mieso 0.3%). The chi-square test (Stat 14.0) was used to determine the strength of potential risk factors associated with the occurrence of brucellosis by using univariable logistic regression. Mixed flock (OR = 2.11 (1.33–3.36 CI; P=0.002)), agropastoral (OR = 4.01 (2.35–6.84 CI; P=0.0001)) and pastoral (OR = 2.59 (1.37–4.90 CI; P=0004)) production system, and larger flock size (OR = 1.68 (1.08–2.60 CI; P=0.021) were factors significantly affecting the prevalence of small ruminant brucellosis. Univariable analysis was used, and independent predictors of small ruminant brucellosis were further analyzed using multilogistic regression. This disease was presented in the current study area; therefore, the careful separation of positive animals would help to prevent and control further distribution of the disease.